PERENCANAAN PEMBANGUNAN DALAM PENGEMBANGAN INFRASTRUKTUR TAMAN BALAI KOTA SURABAYA - Susi Ratnawati; Fierda Nurany; Daniel Maola Robert Dinan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
Development is a series of growth and change efforts that are consciously planned and carried out by the nation, state and government towards modernization in the context of nation-building. a simpler understanding as a process of change in a better direction through planned efforts. Infrastructure on the other hand, means the main support for implementing a process, such as business, development, etc. Qualitative descriptive research is intended to describe and describe existing phenomena, both natural. In addition, descriptive research does not provide treatment, manipulation or changes to the variables studied, but instead describes a condition as it is. The only treatment given was the research itself, which was carried out through observation, interviews and documentation